Prescribed burning in south-eastern Australia: history and future directions. Issue 1 (2nd January 2020) - Morgan, G. W.; Tolhurst, K. G.; Poynter, M. W.; Cooper, N.; McGuffog, T.; Ryan, R.; Wouters, M. A.; Stephens, N.; Black, P.; Sheehan, D.; Leeson, P.; Whight, S.; et al.
ABSTRACT: Fire has been part of the natural environment of south-eastern Australia for tens of millions of years. Aboriginal people used fire selectively, with skill, for many reasons. The removal of Aboriginal people from most of the region after European settlement changed fire regimes and the composition and structure of vegetation. This study explores the history of fire in south-eastern Australia, describes the development of prescribed burning as a forest management tool, and discusses the factors that have influenced changes in fire regimes. It draws on published and unpublished literature and data held by the Forest Fire Management Committee of the Institute of Foresters of Australia. The study finds that the use of prescribed burning in south-eastern Australia in the past 100 years has been driven primarily by political and legal factors. Since 1939, more than 50 public inquiries, reviews and royal commissions have been held into matters concerning the management of fire in landscapes, including prescribed burning. Prescribed burning has been used for wildfire mitigation, agricultural practices (such as stubble reduction and grazing land management), property protection, the maintenance of ecological processes and biodiversity conservation. Prescribed burning in the region has only ever been practised on a small percentage of forest and land each year. The study finds that a substantial body of fire and ecosystem science has been generated in the past 50 years, with rapid technological developments to support prescribed burning and fire management. Research has provided tools and methods for broadscale prescribed burning, but negative public perceptions of fire have prevented the deployment of comprehensive fire management programs in the region. Although much has been achieved, considerable changes are still required in fire management for it to be sustainable and optimal in protecting economic, social and environmental values. The risks to human lives, property, biodiversity and the environment associated with wildfire are increasing in south-eastern Australia due to climate change, and the wider use of prescribed burning is essential for managing these. The increasing extent and occurrence of wildfire disasters in the region indicates that current fire management will not sustain the full range of ecosystem processes and biodiversity, nor reduce to an acceptable level the impact of wildfires on human lives and property. There is compelling evidence for the greater use of prescribed burning to reduce wildfire risks and impacts, rather than committing increasing resources to wildfire suppression. The potential negative impacts of prescribed burning can be managed effectively using existing knowledge and tools. Clear communication of the benefits of prescribed burning can influence political and public opinion in its favour. More investment in training, human capacity and supporting resources is required to safely and effectively deploy prescribed burning more widely to reduce future wildfire risks.